Effects of Quercitrin on PRV-Induced Secretion of Reactive Oxygen Species and Prediction of lncRNA Regulatory Targets in 3D4/2 Cells - Qiuhua Wang; Xiaodong Xie; Qi Chen; Shouli Yi; Jiaji Chen; Qi Xiao; Meiling Yu; Yingyi Wei; Tingjun Hu (MDPI AG, 2022)
Quercitrin is a kind of flavonoid that is found in many plants; it has good antioxidant activity, and can regulate oxidative stress induced by Pseudorabies virus (PRV)-infected cells. In this study, the secretion of reactive oxygen species (ROS) induced by PRV infection was detected by flow cytometry, and RNA expression profiles of the 3D4/2 cells were produced and analyzed by sequenced GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes); the sequencing results were verified by RT-qCR. The results showed that the secretion of ROS induced by PRV infection in 3D4/2 cells could be significantly decreased by quercitrin. The differentially expressed 1055 mRNA, 867 lncRNA, 99 miRNA, and 69 circRNA were detected between the control group and the PRV infection group. The differentially expressed 1202 mRNA, 785 lncRNA, 115 miRNA, and 79 circRNA were found between the PRV+ quercitrin group and the control group. The differentially expressed 357 mRNA, 69 lncRNA, 111 miRNA, and 81 circRNA were obtained between the PRV+ quercitrin group and the PRV group. The significantly differentially expressed mRNAs were mainly involved in cell metabolism, regulatory protein phosphorylation, protein phosphorylation, antioxidation, regulatory phosphorylation, and so on. Among them, the mRNAs related to antioxidant response and oxidative stress were thioredoxin-interacting protein (TXNIP) and nitric oxide synthase 2 (NOS2). According to the network diagram of lncRNA-miRNA-mRNA, two targeted miRNA (ssc-miR-450c-3p and novel-m0400-3p) relationships with TXNIP and NOS2 were screened. This study provides a scientific foundation for further research for the function of quercitrin in anti-virus-induced oxidative stress.